DIFUSI INOVASI TEKNOLOGI TEPAT GUNA DI KALANGAN WANITA PENGUSAHA DI DESA KASONGAN YOGYAKARTA - Siti Fatonah; Subhan Afifi (Jurnal Ilmu Komunikasi, 2008)
In new order era, the role of government was dominant, it was also as key in technology introduction process. Adoption of innovation process of technology product in development was more depended on NGOs or society initative. How is the effect of that changing toward development communication model? This research tries to explore the influence of changing politic and agent innovation diffusion process toward the acceptance of a new technology. This research will also explore how the promotion agent changing in innovation diffusion in influences form or communication model in technology introduction process. Based on research, it is found that politic context and promotion agent changing in innovation diffusion influences appropriate technology acceptance process in woman entrepreneurs in Kasongan Village. In the previous era, government had much role as a promotion agent. But now in reform era, the role as a promotion agent are handled by artists, volunteer, NGOs, Universities (Lectures and student), individual and groups of society. They use communication channel wich the opener. Communication mode which is placed society as a source of innovation diffusion caused the acceptance level innovation product is high among woman entrepreneurs in Kasongan. Generally, woman entrepreneurs who are as research sources accept innovations around themselves. There are many kind of innovation which are used. At a pre production stage (include design for earthenware vessels form, function, coloring and ornament), innovation of a production stage (incude : The use of tool/terchnology which is more sophisticated in making and burning erathware vessel and innovation at a after production (a new strategy development in marketing such as join an exhibition, making, brochure, advertisement in mass media and also internet).